2010
DOI: 10.3892/or_00000871
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance and clinical importance of estrogen receptor α and β in human endometrioid adenocarcinomas

Abstract: Abstract. Human endometrial cancer expresses both the known estrogen receptors (ER-· and ER-ß). The significance of the relative expression of both ER subtypes in endometrial adenocarcinomas remains to be clarified and the usefulness of the determination of the receptor status in endometrial cancer patients is still controversially discussed. Therefore, the aims of this study were the evaluation of the expression patterns of ER-· and ER-ß with the characterization of the prognostic significance in uterine endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
0
19
1
Order By: Relevance
“…FOXA1 þ /ERa À tumors were enriched among tamoxifen-treated patients at the expense of the tumors that are positive for both ERa and FOXA1 (Fisher exact test: P ¼ 0.018). ERa expression strongly associated with endometrial cancer patient survival, in agreement with previous immunohistochemical reports (39,40). In contrast to previous reports (33,34), FOXA1 expression did not associate with survival of endometrial cancer patients, irrespective whether they did (Fig.…”
Section: Interplay Of Foxa1 and Era In Tamoxifen-associated Endometricontrasting
confidence: 53%
“…FOXA1 þ /ERa À tumors were enriched among tamoxifen-treated patients at the expense of the tumors that are positive for both ERa and FOXA1 (Fisher exact test: P ¼ 0.018). ERa expression strongly associated with endometrial cancer patient survival, in agreement with previous immunohistochemical reports (39,40). In contrast to previous reports (33,34), FOXA1 expression did not associate with survival of endometrial cancer patients, irrespective whether they did (Fig.…”
Section: Interplay Of Foxa1 and Era In Tamoxifen-associated Endometricontrasting
confidence: 53%
“…Another study of 315 endometrial adenocarcinoma patients showed a decreased ERα/ERβ ratio to be associated with shorter DFS and OS [63]. In contrast, expression of ERβ alone did not show any correlation with clinicopathological features [65,67]. Thus, prognostic information may only be achieved when ERα and ERβ are analyzed together.…”
Section: Erβ In Endometrial Cancermentioning
confidence: 89%
“…This finding, however, could not be confirmed yet [62]. A decreased ERα/ERβ ratio has been found to be associated with ovarian invasion in a large study comprising 214 endometrial carcinoma samples [65]. Low ERα/ERβ ratios have also been suggested to lead to progression of myometrial invasion [57,64,66].…”
Section: Erβ In Endometrial Cancermentioning
confidence: 93%
“…ER-B is highly expressed in EC with severe myometrial invasion and an important role of this receptor isoform in the progression of myometrial invasion has been suggested (Mylonas 2010). Pertinently an extensive myometrial invasion may be a progeny of EMT which has been implicated in invasive characteristics of endometrial tumors (Montserrat et al 2011).…”
Section: Steroid Hormones and Their Receptorsmentioning
confidence: 99%